Elementary School Teachers' Perception Towards The Implementation of The Independent Curriculumin Elementary School - Rini Syevyilni Wisda (Prodi. Manajemen Pendidikan Islam, Fakultas Tarbiyah, Institut Pesantren Sunan Drajat, 2025)
The independent curriculum is one form of offering to create a learning process, a meaningful learning experience. This study aims to determine how teachers perceive the implementation of the independent learning concept according to the characteristics and uniqueness of the independent curriculum. The method used is a descriptive qualitative method through a phenomenological approach. The data collection process is through interviews and documentation. That the teacher's perception of the implementation of the curriculum is that teachers are enthusiastic and respond positively to the new curriculum, and really appreciate the implementation of the curriculum, more attention is needed in the implementation of the independent curriculum at SD Rayon III, namely, the experience of teachers in teaching, teacher education who teach, competency development or teacher training on the independent curriculum, so that they are able to design the advantages of the independent curriculum. It is concluded that teacher perception is one of the influences on the implementation of the independent curriculum.